IMPLEMENTASI STRATEGI INFORMATION SEARCH PADA MAHASISWA PRODI PAI MELALUI PEMANFAATAN LITERASI DIGITAL DI MASA PANDEMI COVID-19 - Novita Nur Hamidah (Edu Global : Jurnal Pendidikan Islam, 2021)
For more than a year, the COVID-19 pandemic has become one of the outbreaks of infectious diseases in the world, including in Indonesia. The Indonesian government will continue to limit community activities if the number of positive COVID-19 patients increases. Of course this can affect growth and development in various lives. One of them is the field of education which will also cause problems for students, not PAI study program students. This study aims to determine the form of implementation of the information search strategy for PAI study study students through the use of digital literacy during the COVID-19 pandemic. The method used by the author in this research is descriptive qualitative with a library research approach. From this research, we get a result that finding strategic information is needed to be applied during the COVID-19 pandemic in the distance learning system. Especially for PAI study program students who are easy to have insight or broad information about Islamic material even though they have to study independently. Therefore, to support the ongoing information search strategy, it must also be accompanied by the use of digital literacy during the COVID-19 pandemic. This is where the connection between the implementation of the information search strategy for PAI study study students and the use of digital literacy during the pandemic